Validity of the Human System Audit Transformational Leadership Short Scale (HSA-TFL) in four european countries - Berger, Rita; University of Barcelona (2010)
This study aimed to clarify the validity of the short scale of Transformational Leadership used by the Human System Audit (short HSA-TFL). The need of today’s enterprises for combined assessment of transformational leadership and quality-related performance in wider contexts requires short instruments based on scientific research. Convergent, construct and criterion validity of the short HSA-TFL were analyzed. Comparison of the short HSA-TFL with the Multifactor Leadership Questionnaire (MLQ-5X) showed high convergent validity. Exploratory factor analysis with hospital workers in Spain (N=625) showed the single factor structure of the Spanish version of the HSA-TFL. Confirmatory factor analysis using three further samples of hospital workers (N= 776) from different european countries confirmed a single factor. As regards criterion validity, the results indicated that the short HSA-TFL is positively related in all four countries to subjective performance. In sum, the results provide empirical evidence for the validity of the short HSA-TFL scale.